The Formation of a Multifilament System Driven by Photospheric Converging Motions in a Bipolar Sunspot - Haitang Li; Jinhan Guo; Xin Cheng; Chang Zhou; Xiaoli Yan; Jun Chen; Yang Guo; Jacob Oloketuyi; Mingde Ding; Yu Liu (The Astrophysical Journal Letters, 2025)
Solar filaments are believed to be a clump of cold plasma accumulated in the magnetic dips. However, the magnetic configuration of filaments and the key factors for their formation remains elusive. In this Letter, we present a detailed study of the formation and eruption of a multifilament system with observations and simulations. Before the filament appeared visible, the chromospheric fibrils gradually gathered together, evolving from a diffuse distribution into threadlike structures that were nearly parallel to the polarity inversion lines. On 2022 March 20, an arch filament first appeared showing high dynamics, and subsequently two reserved S-shaped filaments were visibly observed. These two filament segments further reconnected, forming a long coherent filament and resulting in a double-decker configuration. In addition, continuous converging motion and magnetic flux cancellation were found in the photosphere during the evolution. Simultaneously, more bald patch structures appeared at the polarities' collision position. Through a data-driven numerical simulation, we further reconstructed the coronal magnetic field, which is composed of two twisted magnetic flux ropes (MFRs) with their bottom touching the photosphere, along with a group of sheared arcades forming an X-shaped configuration. These findings suggest that the magnetic configuration of the filament is in a highly dynamic state, evolving from a hybrid to a coherent MFR. Moreover, we propose that the formation and eruption of the multifilament system are closely related to magnetic reconnection taking place on the photosphere and in the lower corona, respectively, both mainly driven by the photospheric converging motion.